Number 50 (October 2008) - Southern Fishes Council (Southeastern Fishes Council Proceedings, 2008)
(October 2008) - Use of Visible Implant Fluorescent Elastomer (VIE) Tag Technique on Darters (Teleostei: Percidae): Mortality and Tag Retention. By Joyce A. Coombs and J. Larry Wilson Diversity and Distribution of Native Freshwater Mussels in Bayou Bartholomew, Arkansas. By Jeff A. Brooks, Russell L. Minton, Steven G. George, David M. Hayes, Ronnie Ulmer, and Frank Pezold A Note on Three Collections of Cyprinodontid Fishes Housed in the British Museum of Natural History, Including Syntypes and Historically Important Specimens. By Royal D. Suttkus and James D. Williams Minutes, Business Meeting, 33rd Annual Meeting, Southeastern Fishes Council Regional Southeastern Fishes Council Reports
Keywords: visible implant fluorescent elastomer; tag; VIE; darters; teleostei; percidae; mortality; native freshwater mussels; mussels; bayou bartholomew; arkansas; cyprinodontid; fishes